FRI0499 Real-world study on the patterns and cost of treatment failure in patients with psoriatic arthritis using us claims data. (15th June 2017) - Price, K; Alemao, E; Burns, L; Guo, Z; Anupindi, V; Goday, S
Abstract : Background: Current treatments for psoriatic arthritis (PsA) are associated with a range of limitations, e.g. side effects, safety concerns and inadequate efficacy. The economic burden of biologic (b)DMARD failure among patients (pts) with PsA is thought to be substantial, 1 but there is a need to quantify this formally. Objectives: To evaluate PsA treatment failure (i.e. discontinuation and switching rates) in a US managed care setting and its economic consequences. Methods: Pts aged ≥18 years with 2 diagnosis codes for PsA and 1 claim for a bDMARD from 1 Jan 2007 to 31 Mar 2015 in the Truven Health MarketScan® Database (Commercial and Supplemental Medicare) were eligible for the study. Pts were considered incident if they did not have a PsA diagnosis or a bDMARD prescription during 1 year prior to first PsA diagnosis in the study period, and as prevalent otherwise. Pts had a 1-year follow-up from first PsA diagnosis in the study period. The percentages of pts discontinuing a drug, switching to another drug or continuing on the same drug for 1 year from first date of treatment were reported. Healthcare costs for 1 year from initiation of the first bDMARD, (medical and drug costs associated with treatment failures) were reported as cost per-pt-per-month (PPPM), and a generalized linear model was used to analyse the cost after controlling for various demographic variables. Results: Of the 18, 632 pts treated with a bDMARD, 1298 (6.97%) were incident and 17, 334 (93.03%) prevalent. Almost half (n=8994; 48.27%) of the pts continued on the index bDMARD for 1 year. Treatment failed for the remaining pts, with 7852 (42.14%) discontinuing, and 1630 (8.75%; overlap ≤30 days between drugs) and 156 (0.84%; overlap >30 days) switching. In the prevalent group, 8754 (50.50%) pts continued on the index drug, 7043 (40.63%) discontinued, and 1399 (8.07%; overlap ≤30 days) and 138 (0.79%; overlap >30 days) switched to another drug. Among incident pts, only 240 (18.49%) continued, 809 (62.33%) discontinued, and 231 (17.80%; overlap ≤30 days) and 18 (1.38%; overlap >30 days) switched to another drug. Pts with an overlap >30 days were excluded from the analysis. Overall, pts who switched had a higher PPPM total cost (3317) than those who discontinued (2650; p<0.0001) or continued (2708; p<0.0001). Similar results were observed in the prevalent and incident groups, respectively, with pts who switched incurring a higher PPPM total cost (3241 and 3779) compared with those who discontinued (2583 and 3237; both p<0.0001) or continued (2700 and 3080; both p<0.0001). Increasing age (per year) was associated with a 0.57% higher total cost in the incident group (p=0.002) and with a 0.49% higher cost in the prevalent group (p<0.0001). Among prevalent pts, females had a 3.08% higher cost than males (p=0.0069). The Charlson Co-morbidity Index score predicted a higher cost (p<0.0001) among prevalent but not incident pts. Conclusions: In a US claims study population of pts with PsA, rates of treatment failure as defined by switching or discontinuation were high. Follow-up costs for pts who switched were higher than for pts who continued or discontinued their medication. Baseline age, female sex and co-morbidities were associated with higher treatment costs. References: Taylor PC, et al. Rheumatol Int 2016;36:685–95. Disclosure of Interest: K. Price Employee of: Bristol-Myers Squibb, E. Alemao Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, L. Burns Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, Z. Guo Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, V. Anupindi: None declared, S. Goday: None declared